Analysis Of Glass Ceiling And Sustainable Business Optimization For Women Entrepreneurial Careers - Puspitaloka Mahadewi, Erlina; Mandala Putra, Juniawan; Reza Hilmy, Mohamad (International Journal of Science, Technology & Management, 2024)
These study reports the comprehensive study about rebuilt the business resilience is very important to achieve the rise industry, with women entrepreneurs because of their important role in the rising of national economy. Most business organizations in Indonesia have experienced disruption caused by the covid-19 pandemic, not a few have ended up bankrupt and unable to survive. For this reason, businesswomen need to manage marketing activities with adaptation and flexible innovation in accordance with the potential of MSMEs through current agile business and marketing strategy. This research aims to formulate a framework for business revival after a crisis such as Covid-19. It is hoped that this research can provide input regarding effective procedures for business organizations in dealing with business disruption for women business owners. This research aims to formulate a framework for business women entrepreneurs’ revival during and after a crisis like covid-19 with qualitative method. A qualitative descriptive approach was used in this research to obtain an overview of the situation experienced by MSMEs. The data collection methods used were interviews, observation, and documentation, using a purposive sampling method in selecting research sources. Source triangulation and technique triangulation methods were used in this research to ensure data validity. The data source for this research is 10 female business MSME owners in Tangerang Banten Indonesia. The results of this research show that agile, adaptation, and innovation, can be used as solutions to deal with business disruption and solutions in business optimization